2018
DOI: 10.1152/jn.00299.2018
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane and ketamine differentially influence spontaneous and evoked laminar electrophysiology in mouse V1

Abstract: General anesthesia is ubiquitous in research and medicine, yet although the molecular mechanisms of anesthetics are well characterized, their ultimate influence on cortical electrophysiology remains unclear. Moreover, the influence that different anesthetics have on sensory cortices at neuronal and ensemble scales is mostly unknown, and represents an important gap in knowledge that has widespread relevance for neural sciences. To address this knowledge gap, this work explored the effects of isoflurane and keta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 90 publications
9
59
0
Order By: Relevance
“…Developing a neural interface model in mice is critical due to the availability of transgenic and disease models, thus increasing the impact for future studies untangling mechanisms of various diseases. A focus was also placed on awake, non-anesthetized recordings, since anesthesia is known to alter neural activity (Brown et al 2010;Michelson & Kozai 2018;Uhrig et al 2018) and adjusting the isoflurane concentration can significantly impact vagus nerve activity (Silverman et al 2018). Therefore, to increase spontaneous neural activity and to better model the clinical environment, an awake recording paradigm was developed.…”
mentioning
confidence: 99%
“…Developing a neural interface model in mice is critical due to the availability of transgenic and disease models, thus increasing the impact for future studies untangling mechanisms of various diseases. A focus was also placed on awake, non-anesthetized recordings, since anesthesia is known to alter neural activity (Brown et al 2010;Michelson & Kozai 2018;Uhrig et al 2018) and adjusting the isoflurane concentration can significantly impact vagus nerve activity (Silverman et al 2018). Therefore, to increase spontaneous neural activity and to better model the clinical environment, an awake recording paradigm was developed.…”
mentioning
confidence: 99%
“…(IIIA). The ECoG pattern was normal, similar to isoflurane anesthesia in rats (Michelson and Kozai, 2018) oscillations showed no significant differences between these groups. SDs and PiDs frequency (SDs: 3.8 ±1.9 Hz, PiDs: 2.9±1.3 Hz) and the amplitude from the baseline (SDs: 0.47±0.2 mV, PiDs: 0.48±0.5 mV) and the area below the depolarization wave were similar.…”
Section: Electrophysiological Brain Activity (Iii)mentioning
confidence: 59%
“…Previous findings investigating ketamine in vivo have described differential effects based on brain region (Slovik et al, 2017;Widman & McMahon, 2018), method of investigation (Bojak et al, 2013;Hildebrandt et al, 2017;Schwertner et al, 2018), and emphasized the dose dependency of the observed effects (Ahnaou et al, 2017;Hertle et al, 2016;Macdonald et al, 1987). These diverse observations have reported frequency-specific increases or decreases also for the beta, theta and alpha band.…”
Section: Resultsmentioning
confidence: 99%
“…One commonly used surgical anesthetic in systems physiology is ketamine-an N-methyl-D-aspartate (NMDA) receptor antagonist-which enters the open receptor channel inhibiting ionic exchange (Anis et al, 1983;Macdonald et al, 1987). One main effect of ketamine thereby is a persistent increase in cortical glutamate which renders cells more excitable (Miller et al, 2016;Zhang et al, 2019) and disinhibition of the cortex through suppression of GABAergic interneurons (Behrens et al, 2007;Homayoun & Moghaddam, 2007;Schobel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%